2019
DOI: 10.1021/acscatal.9b02115
|View full text |Cite
|
Sign up to set email alerts
|

Active Oxygen Species Promoted Catalytic Oxidation of 5-Hydroxymethyl-2-furfural on Facet-Specific Pt Nanocrystals

Abstract: The aerobic oxidation of alcohols and aldehydes over noble metal catalysts is a critical reaction for the catalytic conversion of carbohydrates into value-added chemicals from biomass. However, to fully understand the reaction mechanism, in particular the role of O2 and the generated active oxygen species in these reactions is still a challenging target. In the present work, the sub-10 nm Pt nanocrystals with cubic (Pt-NCs), octahedral (Pt-NOs) and spherical (Pt-NSs) morphologies were synthesized and used as c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 51 publications
1
45
0
1
Order By: Relevance
“…It was reported that the desorption temperature of HMF is less than 200 °C since it would be pyrolyzed to CO 2 and H 2 O subsequently. [ 4a,18 ] Therefore, the HMF‐TPD measurement was conducted between 75 and 200 °C. The Ir‐Co 3 O 4 showed higher desorption temperature (144 °C) for HMF molecules than Co 3 O 4 (108 °C), implying stronger HMF adsorption.…”
Section: Figurementioning
confidence: 99%
“…It was reported that the desorption temperature of HMF is less than 200 °C since it would be pyrolyzed to CO 2 and H 2 O subsequently. [ 4a,18 ] Therefore, the HMF‐TPD measurement was conducted between 75 and 200 °C. The Ir‐Co 3 O 4 showed higher desorption temperature (144 °C) for HMF molecules than Co 3 O 4 (108 °C), implying stronger HMF adsorption.…”
Section: Figurementioning
confidence: 99%
“…2(a) further demonstrates that the choices preference of soluble bases in the HMF oxidation reactions listed in Tables 1-3 were closely correlated with reaction time and temperature, although determined primarily by the activity of catalysts. The structural parameters of catalysts like particle size, exposed crystal planes, and metal-support interaction have obvious effects on the reaction turnover frequency [25][26][27][28][29][30][31][32]. Siyo et al [25] reported that the Pd nanoparticles (NPs) with a mean diameter of 1.8 nm in an alkaline aqueous solution (T = 90°C, p O2 = 0.1 MPa) afforded up to 90% yield of FDCA.…”
Section: Single Noble Metal Catalystsmentioning
confidence: 99%
“…However, the situation is different for the single-crystalline Pt nanocrystals with particle size of sub-10 nm. Yu et al [28] found that Pt-NCs enclosed by the (100) facets exhibited higher catalytic activity compared with Pt-NOs enclosed by the (111) facets and Pt nanospheres (Pt-NSs), mainly due to the fact that OH created on Pt(100) facet is more active for the dehydrogenation of HMFCA to form FFCA compared with the O 2 generated on Pt (111) facet. Recently, Jiang et al [29] found that the activity in the productivity of FDCA by the atomic Pd catalyst supported on MnO 2 was over twice that of its Pd nanoparticle counterpart.…”
Section: Single Noble Metal Catalystsmentioning
confidence: 99%
“…For example, Yu and coworkers investigated the facet-dependent activity of Pt metal by employing sub-10 nm Pt nanocrystals with nanooctahedral (PtÀ NO), nanocubic (PtÀ NC), and nanospherical (PtÀ NS) morphologies. [80] Pt nanocrystals were prepared using a polyol alcohol method, which involves the dropwise addition of a solution of AgNO 3 , H 2 PtCl 6 .6H 2 O, and PVP into the boiling ethylene glycol. The nanocrystals with different morphologies were prepared by changing the concentration of AgNO 3 and by varying the refluxing time.…”
Section: Size-dependent Catalytic Behavior Of Supported Transition Metal Nanoparticle In Hmf Oxidationmentioning
confidence: 99%